Evaluation of knowledge regarding malnutrition and its prevention among mothers in rural areas of Uttarakhand: a cross-sectional study - Anuradha; Anushka; Ayushi; Jyoti; Kajal; Liza; Monika; Sakshi; Shabnam; Shourya; Chandan Kumar; Shama Praveen; et al. (International Journal Of Community Medicine And Public Health, 2026)
Background: Childhood under-nutrition is a major cause of child mortality in India. By providing appropriate nursing care and prompt interventions, mothers can prevent malnutrition among children. This study aimed to assess the knowledge of mothers regarding childhood malnutrition and its prevention. Methods: A cross-sectional study was conducted among mothers in Dehradun, Uttarakhand, to evaluate their knowledge related to malnutrition and its prevention. One hundred mothers were selected using purposive sampling technique through door-to-door visit. Data were collected using structured knowledge questionnaire. Results: Most mothers (92%) had basic understanding of malnutrition. About 70% of mothers were aware of importance of balanced diet in prevention of malnutrition. 61% of mothers were unaware of duration of exclusive breastfeeding and 77% were unaware of exact age of weaning among infants. 90% of the mothers recognized weight loss as the major symptom of malnutrition among children and were unaware of other symptoms of malnutrition such as stunting and edema. Conclusions: The study revealed that majority of the mothers possessed a basic understanding of malnutrition and recognized weight loss as its primary symptom. However, significant knowledge gaps remain regarding exclusive breastfeeding duration, appropriate weaning age, and other signs of malnutrition such as stunting and edema. Strengthening maternal education on infant feeding practices and comprehensive malnutrition indicators is essential for improving child health outcomes.